2021
DOI: 10.1007/s00380-021-01949-1
|View full text |Cite
|
Sign up to set email alerts
|

Disparate effects of ankle-brachial index on mortality in the ‘very old’ and ‘younger old’ populations-the PolSenior survey

Abstract: To assess the relationship between ankle-brachial index (ABI) and up to 10-year mortality in older individuals below and above the age of 80 years. In a multicenter survey of health status in the community dwelling subjects aged 55–59 and 65 + years in Poland, we assessed baseline medical history including risk-factors. We measured ABI, and serum creatinine, cholesterol, NT-proBNP, and interleukin-6 (IL-6) concentrations. We assessed mortality based on public registry. Between 2009 and 2019, 27.3% of 561 parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…ABI < 0.9 is a sign of PAD, 1.4 > ABI ≥ 0.9 is considered normal, while ABI ≥ 1.4 corresponds to stiff arteries. In earlier research, we did not demonstrate 9-year difference in mortality between the 1.4 > ABI ≥ 0.9 and the ABI ≥ 1.4 groups of older persons [ 9 ]. Previously, we demonstrated the age dependent fashion for the relation between ABI and mortality in older persons [ 9 ].…”
Section: Introductionmentioning
confidence: 77%
See 2 more Smart Citations
“…ABI < 0.9 is a sign of PAD, 1.4 > ABI ≥ 0.9 is considered normal, while ABI ≥ 1.4 corresponds to stiff arteries. In earlier research, we did not demonstrate 9-year difference in mortality between the 1.4 > ABI ≥ 0.9 and the ABI ≥ 1.4 groups of older persons [ 9 ]. Previously, we demonstrated the age dependent fashion for the relation between ABI and mortality in older persons [ 9 ].…”
Section: Introductionmentioning
confidence: 77%
“…In earlier research, we did not demonstrate 9-year difference in mortality between the 1.4 > ABI ≥ 0.9 and the ABI ≥ 1.4 groups of older persons [ 9 ]. Previously, we demonstrated the age dependent fashion for the relation between ABI and mortality in older persons [ 9 ]. We also found that the abnormalities during PHEA are prevalent in persons with greater ABI [ 10 ].…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation
“…Since LSFG shows skin blood flow as a relative value, it is difficult to use the raw value for comparison between individuals. ABI is a simple and effective test, as there are reports that major amputation may be avoided when endovascular therapy improves ABI by 0.15 or more [6] and that mortality rate in ABI < 0.9 increases more than in ABI > 0.9 [7]. To make the ratio like ABI, the measured In setting the ROI, 12 points that were easily discerned anatomically from the body surface were chosen.…”
Section: Discussionmentioning
confidence: 99%
“…In a prospective study in Spain on 5679 patients, 5517 (97.1%) had a normal ABI, while 162 (2.9%) had ABI≥1.4 [22], which is consistent with the results of the present study. A study by Królczyk in Poland on the different effects of ABI on mortality in older patients, 118 participants had a low ABI (13.9%), 662 had a normal ABI (77.7%), and 72 had a high ABI (8.4%) [23].…”
Section: Discussionmentioning
confidence: 99%